Challenges in Idiopathic Pulmonary Fibrosis Management - George Nyale; Stefanni Paraguas; Shereen Khan; Syed Munis Ul Hasan; Jahanzeb Kamal Khan; Maqbool Ahmed; Dhamith Nandadeva; Andrew Owuor; Sumedha Heenagamage (Journal of the Pakistan Medical Association, 2023)
Objective: The authors aim to evaluate the challenges faced by each stakeholder for Idiopathic pulmonary fibrosis (IPF) management, including the patients, their families/caretakers, Healthcare professionals, and Healthcare policymakers and organizations in Lowmiddle income countries (LMICs) as perceived by 140 pulmonologists from 11 countries who participated in International Respiratory Forum conference 2022 in Ho Chi Minh City, Vietnam. Methodology: A predesigned structured questionnaire was developed about challenges faced by each stakeholder for IPF management. Study participants were randomly divided into four groups, and only one section of the questionnaire was distributed among the participants of each group. Results: It was observed that the physicians greatly supported the psychological well-being of the patients/caregivers and awareness among Healthcare professionals (HCPs) for timely referrals and diagnosis. The caregivers must support the patients to keep their willpower intact. The availability of only those therapies with modest treatment outcomes with no benefits in halting the disease or reducing mortality and the absence of disease-modifying drugs was considered the major challenge faced by Pulmonologists. Patient affordability was considered the key hindering factor affecting High- Resolution Computed Tomography (HRCT) utilization. The development of Interstitial lung disease (ILD) national registries to keep track of disease prevalence and challenges at hand was defined as the urgent healthcare initiatives that need to be taken by the concerned healthcare policymaking authorities. Moreover, the healthcare systems considered comprehensive patient education about disease management and outcomes the most effective self-management strategy to be incorporated and disseminated. Although a small number of patients with ILDs, specifically IPF, receive a prompt and accurate diagnosis, the survey found that protracted delays, frequent misdiagnoses, exposure to expensive and invasive diagnostic procedures, and significant use of healthcare resources mark the more typical diagnostic experience for those with ILD. Conclusion: These findings indicate the requirement for novel diagnostic tools, best clinical practices, and HCPs training to improve the accuracy of diagnoses in ILD patients. Keywords: Idiopathic Pulmonary Fibrosis, Management, Challenges.